Binary Systems of Acetone with Chloroalkanes, Benazene Cyclohexane, Chlorobenzene and Alkanols - N. Modi, Ashvin; Desai, C.M. (Asian Journal of Chemistry, 2010)
Spectral absorbance of dye indicator for binary mixtures of acetonewith cbloroalkanes, benzene, cblorobenzene, cyclohexane andvarious alkimols indicates molecular interactions among these liquids;some of them indicate higher absorbance and others havelower while some do not show no interactions.